Monoclonal antibodies against the 43,000 da glycoprotein from Paracoccidioides brasiliensis modulate laminin-mediated fungal adhesion to epithelial cells and pathogenesis - Gesztesi, J. L.; Puccia, R.; Travassos, L. R.; Vicentini, A. P.; deMoraes, J. Z.; Franco, M. F.; Lopes, J. D. (Mary Ann Liebert, Inc., 1996)
The surface glycoprotein gp43, a highly immunogenic component of Paracoccidioides brasiliensis, is used in the serodiagnosis of paracoccidioidomycosis (PCM) and has recently been shown to specifically bind the extracellular matrix protein laminin, Binding to laminin induces the increased adhesion of the fungus to epithelial cells; a hamster testicle infection model has shown that the gp43-dependent binding of fungal cells to laminin enhances their pathogenicity in vivo. We report on the production and characterization of 12 monoclonal antibodies against the gp43 that recognize peptide sequences in the molecule detecting at least three different epitopes as well as different isoforms of this antigen. MAbs interfered in the fungal pathogenicity in vivo either by inhibiting or enhancing granuloma formation and tissue destruction, Results suggest that P. brasiliensis propagules may start infection in man by strongly adhering to human lung cells, Thus, laminin-mediated fungal adhesion to human lung carcinoma (A549) cells was much more intense than to Madin-Darby canine kidney cells (MDCK), indicating differences in binding affinity, Subsequent growth of fungi bound to the lung cells could induce the granulomatous inflammatory reaction characteristic of PCM. Both steps are greatly stimulated by laminin binding in infective cells expressing gp43.